The Holocaust: A Mizrahi Perspective - Oppenheimer, Yochai (Hebrew studies, 2010)
Second Generation Mizrahi writers reject the Holocaust as an Israeli narrative (both national and Ashkenazi) that overshadows their own history and forces them to be integrated into a national story. They also reject the writing of first generation authors and their emotional identification with the Holocaust stories of European Jewry, claiming it must come at the expense of their unique Mizrahi perspective that will transcend the borders of the hegemonic representation. This dual rejection—of hegemonic Ashkenazi fiction and of first-generation Mizrahi writers—is evident in two alternative directions adopted by second generation Mizrahi writers. , One direction is political-critical. Writers such as Dudu Busi, Kobi Oz, and Orly Castel-Bloom examine both the temptation and the danger threatening Mizrahim who imagine they can become Israelis by adopting hegemonic (Ashkenazi) models of Israeliness, so losing their own ethnic consciousness within the hegemonic national Holocaust discourse. , The other direction is humanistic-ethnic. Writers such as Amira Hess and Sami Berdugo clarify that the political perspective of the Holocaust as solely an Israeli narrative or as a means of cultural control is inadequate, and demand that an additional, complementary viewpoint be considered. This complementary stance views the Holocaust as a necessary basis for understanding the experience of immigration and displacement of both European and Mizrahi Jews. This is an attempt to understand the Mizrahi migration, and particularly the trauma that accompanied it for over a generation, through the metaphor of the Holocaust.